Understanding and Remediating Social-Cognitive Dysfunctions in Patients with Serious Mental Illness Using Relational Frame Theory - Hendriks, Annemieke L.; Barnes-Holmes, Yvonne; McEnteggart, Ciara; De Mey, Hubert R. A.; Janssen, Gwenny T. L.; Egger, Jos I. M. (Frontiers in Psychology, 2016)
Impairments in social cognition and perspective-taking play an important role in the psychopathology and social functioning of individuals with social anxiety, autism or schizophrenia-spectrum disorders, among other clinical presentations. Perspective-taking has mostly been studied using the concept of Theory of Mind (ToM), which describes the sequential development of these skills in young children, as well as clinical populations experiencing perspective-taking difficulties. Several studies mention positive results of Theory of Mind based training programs, however, the precise processes involved in the achievement of these improvements are difficult to determine. Relational Frame Theory (RFT) is a modern behavioural account of complex cognitive functions, and is argued to provide a more precise approach to the assessment and training of perspective-taking, among other relational skills. Results of RFT-based studies of perspective-taking in developmental and clinical settings are discussed. The development of training methods targeting perspective-taking deficits from an RFT point of view appears to provide promising applications for the enhancement of current treatments of people with social-cognitive dysfunctions.